Digital methods for measuring grain size parameters of aggregate–binder mixtures. - Profitis, E.; Kapatos, D.; Chatzitheodoridis, E.; Xirouchakis, D.; Loupasakis, C. (Bulletin of the Geological Society of Greece, 2013)
Geometrical parameters of natural and crushed aggregates such as grain length, perimeter, area, etc., underline the shape and flakiness indices definition. The latter indices have a measurable effect on the mechanical properties of aggregates–binder mixtures, e.g. concrete, mortar, bituminous mixtures. In this work, digital methods were developed with the mathematical software Matlab, by applying a statistical method called k-means clustering for the exact separation between background and aggregates to compute the aforementioned properties. The overall code can be applied in real time by analysing quickly a large volume of data with accuracy and significant cost reduction. Currently, only the two dimensions of the grains could be measured. Future work will focus on full three-dimensional measurements by comparing paired images taken from different angles but also aggregate segmentation in case of touching particles.